ANALISIS SEKTOR UNGGULAN DI KOTA MEDAN - Rebecka Octaria N; Paidi Hidayat (Ekonomi dan Keuangan, 2015)
The purpose of this study was to determine the centers of economic growth in the city of Medan through analysis of a typology Klassen, schallogram analysis and analysis of gravity. Based on the results obtained Klassen Typology and schallogram in Medan that there are two centers of growth ithat are District of Medan Deli District of Medan Petisah. Based on gravity analysis shows that the sub-district at the center of that growth has the strongest interaction of Medan Deli District is Medan Timur District and the strongest interaction of Medan Petisah District is Medan Helvetia District.Keywords: Based Sector